2019
DOI: 10.1038/s41377-019-0131-4
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative imaging of the complexity in liquid bubbles’ evolution reveals the dynamics of film retraction

Abstract: The dynamics and stability of thin liquid films have fascinated scientists over many decades. Thin film flows are central to numerous areas of engineering, geophysics, and biophysics and occur over a wide range of lengths, velocities, and liquid property scales. In spite of many significant developments in this area, we still lack appropriate quantitative experimental tools with the spatial and temporal resolution necessary for a comprehensive study of film evolution. We propose tackling this problem with a ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 46 publications
1
24
0
Order By: Relevance
“…In conclusion, we measured the proximity effect of the wall on the sedimentation of colloidal microspheres near the surfaces with different slip lengths by the use of digital holographic microscopy (DHM). DHM provides quantitative phase-contrast and 3D imaging in arbitrary time scales, which makes it a suitable method to investigate various phenomena, including the dynamic behavior of colloids in 3D 22 – 24 , 60 62 . We have observed that for lower slip length values, the proximity effect is more pronounced, while the falling velocity variation of the particles increases by the slip length of the wall.…”
Section: Resultsmentioning
confidence: 99%
“…In conclusion, we measured the proximity effect of the wall on the sedimentation of colloidal microspheres near the surfaces with different slip lengths by the use of digital holographic microscopy (DHM). DHM provides quantitative phase-contrast and 3D imaging in arbitrary time scales, which makes it a suitable method to investigate various phenomena, including the dynamic behavior of colloids in 3D 22 – 24 , 60 62 . We have observed that for lower slip length values, the proximity effect is more pronounced, while the falling velocity variation of the particles increases by the slip length of the wall.…”
Section: Resultsmentioning
confidence: 99%
“…[ 19–23 ] To evaluate bubbles’ evolution, radius and shell thickness are the commonly used structural parameters, while bubbles’ shell thickness can hardly be accurately measured by normal optical microscope. [ 23,24 ] At present, different techniques have been proposed and implemented to monitor the film thickness's alteration. [ 24,25 ] For instance, interferometry is engaged to analyze the fringes formed by the interference of reflected light from the thin film's two interfaces.…”
Section: Introductionmentioning
confidence: 99%
“…[ 23,24 ] At present, different techniques have been proposed and implemented to monitor the film thickness's alteration. [ 24,25 ] For instance, interferometry is engaged to analyze the fringes formed by the interference of reflected light from the thin film's two interfaces. Though the technique can measure the film thickness over a large area in a real‐time manner, it can hardly provide more geometrical information about an evolving microbubble as a whole.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Herein, we tackle this problem using a holographic technique that combines quantitative phase imaging with a custom setup designed to form and manipulate bubbles [5]. digital holography (DH) is often used in sensors and microscopes to assess small variations of concentration [6], cell mass profiling [7] or thickness in transparent samples below the diffraction limit [8,9].…”
Section: Introductionmentioning
confidence: 99%